Allied in danger [compact disc, unabridged] : a capital crimes novel - Truman, Margaret, 1924-2008; Truman, Margaret, 1924-2008 (Capital crimes, 2018)
David Portland works security for America's British Embassy in London. His life is upended when his son Trevor dies mysteriously in Nigeria, while employed by a suspicious security/mercenary company known as SureSafe. One night, Portland sees a man in a bar wearing a bracelet--a family heirloom, which he had given his son--and attacks the man. The information he learns will send Portland down a rabbit-hole of deadly deception--one which he hopes will lead him to the truth about his son's death. Meanwhile, Robert Brixton, a noted Washington DC-based international investigator, has been hired to look into a fraudulent charity and a criminal warlord in Nigeria. His life and his investigations will soon become intertwined with Portland's probe and that of his estranged, ex-wife, Elizabeth. Their interconnected cases will take Brixton to Nigeria, into that country's Heart of Darkness and on one of the most violent and dangerous journeys of his life.